2022
DOI: 10.1073/pnas.2116543119
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the key role of Pt···Pt interactions in the directional self-assembly of platinum(II) complexes

Abstract: Significance Molecular self-assembly provides a bottom-up platform to design supramolecular functional materials, attracting numerous interests in material sciences. The utilization of platinum(II) complexes as building blocks of supramolecular assemblies opens up the unique noncovalent Pt···Pt interaction as one of the driving forces, imparting the supramolecular materials with rich spectroscopic features. However, the exact role of Pt···Pt interactions in molecular assembly remains elusive. The cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 65 publications
2
40
0
Order By: Relevance
“…). Recently, Yam and co-workers 71 showed that the self-assembly of Pt( ii ) complex is the result of metallophilic interaction between two Pt( ii ) centres. Such assemblies often exhibit red-shifted absorption (along with new metal–metal-to-ligand charge transfer MMLCT transition) and emission, as well as enhanced quantum yield and longer lifetime.…”
Section: Impact Of Ncis On the Structural And Photo-physical Properti...mentioning
confidence: 99%
“…). Recently, Yam and co-workers 71 showed that the self-assembly of Pt( ii ) complex is the result of metallophilic interaction between two Pt( ii ) centres. Such assemblies often exhibit red-shifted absorption (along with new metal–metal-to-ligand charge transfer MMLCT transition) and emission, as well as enhanced quantum yield and longer lifetime.…”
Section: Impact Of Ncis On the Structural And Photo-physical Properti...mentioning
confidence: 99%
“…250−252 Furthermore, the directional role of the noncovalent Pt•••Pt interactions in the self-assembly process has been elucidated through a combination of experimental and computational efforts. 254 The directional Pt•••Pt interactions have been found to be arising from the interactions between the p z and d z 2 orbital pairs, playing an important role in governing the self-assembly processes and kinetics for achieving the formation of ordered self-assembled architectures in an anisotropic manner. 254 Exploitation on metal complexes of Ni(II), 255 Pd(II), 256,257 Rh(I), 185,187,258 Au(III), 259,260 Cu(I), 261,262 Ag(I), 263 and Au(I) 264−267 that are capable of exhibiting metal−metal interactions has opened up new avenues in controlling the strength of the metal−metal interactions and the geometry of the complexes, leading to the development of new classes of supramolecular functional materials.…”
Section: ■ Perspective and Challengesmentioning
confidence: 99%
“…254 The directional Pt•••Pt interactions have been found to be arising from the interactions between the p z and d z 2 orbital pairs, playing an important role in governing the self-assembly processes and kinetics for achieving the formation of ordered self-assembled architectures in an anisotropic manner. 254 Exploitation on metal complexes of Ni(II), 255 Pd(II), 256,257 Rh(I), 185,187,258 Au(III), 259,260 Cu(I), 261,262 Ag(I), 263 and Au(I) 264−267 that are capable of exhibiting metal−metal interactions has opened up new avenues in controlling the strength of the metal−metal interactions and the geometry of the complexes, leading to the development of new classes of supramolecular functional materials. We believe that the design of supramolecular functional materials via sophisticated hierarchical assembly is a fascinating field and requires the collective efforts of researchers to develop new classes of materials with desirable functions, achievable through a fundamental understanding of the strengths and dynamics of the noncovalent interactions.…”
Section: ■ Perspective and Challengesmentioning
confidence: 99%
See 2 more Smart Citations